Ecological suitability of mangrove ecosystems as mangrove rehabilitation areas in the Sei Carang estuary waters of Tanjungpinang City - Rahima Zakia; Febrianti Lestari; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
The waters of the Sei Carang estuary are water areas that are influenced by tides and have mangrove vegetation along the waters. However, with the conversion of land functions such as bauxite mining and logging activities, the existing mangrove ecosystem is damaged. The purpose of the study was to determine the ecological characteristics of the mangrove ecosystem and to determine the level of ecological suitability of the mangrove ecosystem as a mangrove rehabilitation area in the Sei Carang estuary waters, Tanjungpinang City. This study used a purposive sampling method at 4 stations selected based on land openness and locations that allow for rehabilitation. Parameters in this study include mangrove type, substrate, salinity, tidal type, pH, current velocity, and biota objects. Based on observations, there were 10 types of mangroves found. The results of observations that have been calculated using the mangrove rehabilitation land suitability matrix show that each station can be said to be suitable for the rehabilitation area with the distribution of the suitability value of mangrove rehabilitation land showing a dominant suitability of S1 (Highly Appropriate).